Agapetes xiana sp. nov. (Ericaceae) from Xizang, China - Tong, Yi Hua (Phytotaxa, 2016)
Agapetes xiana sp. nov., from Southeast Xizang, China is described and illustrated here. It is similar to A. xizangensis and A. subansirica, but differs from the former by its larger leaves, longer pedicels, smaller calyx lobes, yellowish green corollas and longer stamens, and from the latter by having inflorescences with fewer flowers, much longer pedicels, corollas and stamens. Its taxonomic position is also discussed.